UJI AKTIVITAS ANTIJAMUR EKSTRAK ETANOL DAUN SOM JAWA TERHADAP PERTUMBUHAN Candida albicans UNTUK MENJAMIN MUTU PENGGUNAAN SEBAGAI OBAT HERBAL ANTIKEPUTIHAN - Suharsanti, Ririn; Wibowo, F.X. Sulistyanto (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2016)
ABSTRACT Empirically, leaves and roots of som Java (Talinum triangulare (Jacq.) Willd) has been used as a whiteness medicinal drug efficacious. This study aims to better ensure the quality of ethanolic leaf extract som Java as whiteness herbal medicine based test antifungal activity against Candida albicans growth. The method used was agar diffusion method with PDA (Potatoes Dextrose Agar) were inoculated Candida albicans, then filled with test compounds antimicrobials that are reconstituted with the solvent DMSO extract concentration, incubated for 3x24 hours at a temperature of 25°C, observations were made by measuring the inhibition zone around sinks. Antifungal activity test showed inhibition zone began to extract the solvent DMSO concentration of 40% amounting to 1.380 ± 0.028, increasing the concentration of the inhibitory zones is increasing as well. This is due to the increasing concentration, it also increase the active substance content which are within the extract that can serve as an antifungal